From the Shadows : The Ultimate Insider's Story of Five Presidents and How they Won the Cold War - Gates, Robert Michael, 1943- (New York Simon & Schuster Paperback, 2006)
Robert Gates, former head of the CIA, reveals fascinating insights into how the US Central Intelligence Agency has evolved by recurring trials and errors.
Include Illustration and Index
Keywords: United States -- Soviet Union -- Diplomatic relations